E-MODUL BERBASIS PROBLEM BASED LEARNING MENGGUNAKAN BOOK CREATOR PADA MATERI PERBANDINGAN: E-Module Based on Problem Learning Using Book Creator on Comparative Material - Anggraini, Tri Resia; Hartatiana, Hartatiana; Wardani, Ambarsari Kusuma (Universitas Tadulako, 2023)
This research aims to produce e-module based on problem based learning use book creator on valid and practical comparative material. This research is development research with the ADDIE development model which consists of five stages those five stages is analysis, design, development, implementation, and evaluation. The subjects in this study were 7th grade junior high school students Negeri 4 Gunung Megang. Retrieval of research data by using a material validation sheet, validation media, and interviews as well as a practicality questionnaire. E-module validity data obtained from material validation and validation media with three validators. As for practicality data obtained from the distributed questionnaire to students. The results showed that the validity value of the e-module was 0.84 with a high validity category and the achievement of values ​​for the practicality of e-module 85.13% with very practical category. It can be concluded that e-module based on problem learning using book creator on comparative material produced tested valid and practical.